A NOVEL ORTHOREOVIRUS ASSOCIATED WITH EPIZOOTIC NECROTIZING ENTERITIS AND SPLENIC NECROSIS IN AMERICAN CROWS (CORVUS BRACHYRHYNCHOS) - Forzán, María J.; Renshaw, Randall W.; Bunting, Elizabeth M.; Buckles, Elizabeth; Okoniewski, Joseph; Hynes, Kevin; Melendez, Richalice; Ableman, Ashley; Laverack, Melissa; Fadden, Melissa; Dastjerdi, Akbar; Schuler, Krysten; et al. (Journal of wildlife diseases, 2019)
Epizootic mortalities in American Crows (Corvus brachyrhynchos) during the winter months, referred to as winter mortality of crows, have been recorded in North America for almost two decades. The most common postmortem findings include necrotizing enteritis, colitis, and fibrinous splenic necrosis. These findings are proposed to be due to infection with a Reovirus sp. Our objectives were to characterize the pathology and seasonality of the epizootics in New York State (NYS), confirm the causative role of an Orthoreovirus sp., and determine its phylogeny. On the basis of our proposed case definition for reovirosis, we examined case data collected by the NYS Wildlife Health Program for 16 yr. A total of 558 cases of reovirosis were recorded between 2001 and 2017. Reovirosis had a clear seasonal presentation: cases occurred almost exclusively in winter months (71% in December–January). Detailed data from a 2-yr period (2016–17) demonstrated that reovirosis caused up to 70% of all recorded crow deaths during epizootic months. Crows with positive orthoreovirus isolation from the spleen or intestine were 32 times more likely to die with characteristic histologic lesions of enteritis or enterocolitis and splenic necrosis than crows with negative isolation results. An in situ hybridization probe specific to virus isolated from NYS crow reovirosis cases demonstrated a direct association between viral presence and characteristic histologic lesions. Sigma C (capsid protein) sequences of isolates from NYS crows showed high homology with Tvärminne avian virus, recently proposed as a novel Corvus orthoreovirus clade, and only distantly related to the avian orthoreovirus clade. Our study indicated that a novel orthoreovirus was the cause of winter mortality (or reovirosis) of American Crows and placed the NYS isolates in the newly proposed genus of Corvid orthoreovirus.